PLANNING MARKETING STRATEGY FOR INCREASING SALES USING STRENGTH, WEAKNESS, OPPORTUNITIES AND THREATS-IE MATRIX AND QUANTITATIVE STRATEGIC PLANNING MATRIX - Primasanti, Yunita; Azzat, Noor Nailie; Satria, Bima (Universitas Islam Nahdlatul Ulama Jepara, 2024)
CV Cakra Nusantara is a company engaged in the distribution sector, which cannot be separated from marketing and distribution problems for goods sold to consumers. Some issues include incompetent human resources, high sales turnover, limited unit availability, less strong teamwork, lack of attractive promotional activities, and human resources that have not mastered product knowledge. The need for staple products is constantly increasing every year, the trend of society is still wasteful, the incessant promotion and innovation of competitors, the competitive position in the market is very high, and the economic situation still needs to be fixed. This study aims to determine the strengths and weaknesses from the marketing side and maximize the opportunities owned by combining the SWOT-IE and QSPM methods. Based on the results of an internal environmental analysis, the company's main strengths are relatively cheap product prices and an excellent strategic location, with a score of 0.44444, which can be interpreted as the low price factor and a good distribution system having its strengths for the company. The main opportunities owned by the company are good relations with suppliers from factories and cooperation with new retailers, which are the main opportunities for companies with scores of 0.44 and 0.5. The results of the QSPM matrix analysis obtained alternatives to increase observation of developing markets and increase marketing in product promotion. It is shown by the results of the Total Attractive Score (TAS) of 4.675.PERENCANAAN STRATEGI PEMASARAN UNTUK PENINGKATAN PENJUALAN DENGAN METODE STRENGTH, WEAKNESS, OPPORTUNITIES AND THREATS-IE MATRIX AND QUANTITATIVE STRATEGIC PLANNING MATRIXCV Cakra Nusantara merupakan perusahaan yang bergerak dibidang distributor yang tentunya tidak akan lepas dari masalah pemasaran dan penyaluran barang yang akan dijual ke konsumen.Beberapa masalah antara lain: SDM yang kurang kompeten, tingginya turn over sales, ketersediaan unit yang masih terbatas, Team work yang kurang kuat, Kurang melakukan kegiatan promosi yang menarik, sumberdaya manusia belum menguasai produk knowledge. kebutuhan akan produk bahan pokok setiap tahun selalu meningkat, trend masyarakat yang masih konsumtif, gencarnya promosi dan inovasi pesaing, posisi kompetitif dalam pasar sangat tinggi, situasi perekonomian yang masih belum stabil. Penelitian ini bertujuan untuk mengetahui kekuatan, kelemahan dari sisi pemasaran dan memaksimalkan peluang yang dimiliki dengan menggunakan kombinasi metode SWOT-IE dan QSPM. Berdasarkan hasil analisis lingkungan internal Kekuatan utama yang dimiliki oleh perusahaan terdapat pada harga produk relatif murah dan Lokasi yang strategis yang baik menjadi kekuatan utama bagi perusahaan dengan skor sebesar 0,44444. Yang dapat diartikan bahwa dari faktor harga yang murah dan system distribusi yang baik memiliki kekuatan tersendiri bagi perusahaan. Sedangkan peluang utama yang dimiliki oleh perusahaan terdapat Hubungan baik dengan pemasok dari pabrik dan Kerjasama dengan retail yang baru menjadi peluang utama bagi perusahaan dengan skor sebesar 0,44 dan 0.5. Hasil analisis matriks QSPM diperoleh alternatif meningkatkan observasi terhadap pasar yang berkembang serta meningkatkan marketing dalam promosi produk. Hal ini ditunjukan dengan hasil Total Attractive Score (TAS) sebesar 4,675.